2007
DOI: 10.1016/j.neuroscience.2007.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Decreased infarct size after focal cerebral ischemia in mice chronically infected with Toxoplasma gondii

Abstract: Abstract-To determine whether Toxoplasma gondii infection could modify biological phenomena associated with brain ischemia, we investigated the effect of permanent middle cerebral artery occlusion (MCAO) on neuronal survival, inflammation and redox state in chronically infected mice. Infected animals showed a 40% to 50% decrease of infarct size compared with non-infected littermates 1, 4 and 14 days after MCAO. The resistance of infected mice may be associated with increased basal levels of anti-inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
1
9
0
1
Order By: Relevance
“…For example, it inhibits the development of arthritis in mice deficient in the interleukin receptor antagonist (IL1RN) [106]. T. gondii infection is also able to reduce infarct size in focal cerebral ischaemia in mice, an effect attributed to the ability of infection to increase the expression of nerve growth factor, as well as that of anti-inflammatory cytokines and of glutathione and oxidative stress protective genes, while reducing the expression of proinflammatory cytokines [107]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, it inhibits the development of arthritis in mice deficient in the interleukin receptor antagonist (IL1RN) [106]. T. gondii infection is also able to reduce infarct size in focal cerebral ischaemia in mice, an effect attributed to the ability of infection to increase the expression of nerve growth factor, as well as that of anti-inflammatory cytokines and of glutathione and oxidative stress protective genes, while reducing the expression of proinflammatory cytokines [107]. …”
Section: Resultsmentioning
confidence: 99%
“…Toxoplasma is an intracellular parasite that naturally, persistently, and asymptomatically infects the CNS of both humans and rodents. Three studies have shown that mice chronically infected with one particular strain of Toxoplasma are protected against a second CNS insult ( Arsenijevic et al., 2007 ; Jung et al., 2012 ; Möhle et al., 2016 ). Two of these studies found a > 60% reduction in Aβ deposition in infected mice compared with uninfected AD mice ( Jung et al., 2012 ; Möhle et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This response is analogous to (and overlaps with) ischemic or hyperthermic preconditioning, in which sublethal prestroke stimuli up-regulate a coordinated network of protective genes [31]. Chronic prestroke inflammation can also be protective: chronic preischemic stroke infection of mice with Toxoplasma gondii reduced the subsequent proinflammatory cytokine response, improving outcome and lessening infarct size [32]. Similar results were also shown more recently following induced periodontitis in rats [33].…”
Section: Prestroke Inflammation: Potentiation Versus Protectionmentioning
confidence: 60%